Vitis shizishanensis, a new species of the grape genus from Hubei province, China - Zhi-Yao Ma (Pensoft Publishers, 2021)
Vitis shizishanensis (Vitaceae), a new species from Hubei, China, is described and illustrated. It is morphologically similar to V. flexuosa and V. bryoniifolia, but differs in leaf lobing and pubescence. It can be easily distinguished from the two species based on its glabrous or with very sparse arachnoid tomentum on the abaxial mature leaf surface, and its unlobed to 3–7 lobed leaves. A detailed description, along with photographs for the new species, and a table for morphological comparisons with similar Vitis species, are also provided.